2011
DOI: 10.1158/1078-0432.ccr-11-0687
|View full text |Cite
|
Sign up to set email alerts
|

Specific PET Imaging of xC− Transporter Activity Using a 18F-Labeled Glutamate Derivative Reveals a Dominant Pathway in Tumor Metabolism

Abstract: Experimental Design: Derivatives of L-glutamate were investigated in cell competition assays to characterize the responsible transporter. An automated radiosynthesis was established for the most promising candidate. The resulting 18 F-labeled PET tracer was characterized in a panel of in vitro and in vivo tumor models. Tumor specificity was investigated in the turpentine oil-induced inflammation model in rats.Results: A fluoropropyl substituted glutamate derivative showed strong inhibition in cell uptake assay… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
142
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(148 citation statements)
references
References 44 publications
6
142
0
Order By: Relevance
“…Preclinical studies demonstrated a high uptake of 18 F-FSPG in several tumor cell lines occurring specifically via the system x C 2 , a sodium-independent transporter, which has an increased activity in tumors (7). Proof-ofmechanism studies are currently under way describing promising results in humans, which will be important for the further development of 18 F-FSPG as an imaging agent in cancer.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Preclinical studies demonstrated a high uptake of 18 F-FSPG in several tumor cell lines occurring specifically via the system x C 2 , a sodium-independent transporter, which has an increased activity in tumors (7). Proof-ofmechanism studies are currently under way describing promising results in humans, which will be important for the further development of 18 F-FSPG as an imaging agent in cancer.…”
Section: Discussionmentioning
confidence: 97%
“…The specificity of uptake was demonstrated recently in cell competition assays and cells with transporter knockdown (6). An excellent tumor visualization was achieved in animal tumor models (7). Biodistribution analysis in rodents showed a rapid blood clearance via the kidneys and low background activity (including in the brain), providing high contrast for tumor imaging (7).…”
mentioning
confidence: 99%
“…Glutamate, glutamine, and glutamic acid PET radiotracers have been developed (69). Progress has been made with a system X 2 c glutamate derivative PET radiotracer, (4S)-4-(3-18 F-fluoropropyl)-L-glutamate ( 18 F-FSPG), with which primary prostate cancer in 5 of 10 patients and recurrent or metastatic prostate cancer in 7 of 10 FIGURE 3.…”
Section: Emerging Amino Acid-based Pet Radiotracersmentioning
confidence: 99%
“…18 F-FSPG was radiolabeled as described previously (9). The specific activity of 18 F-FSPG formulated for intravenous administration was 74.4 6 59.6 GBq/mmol (range, 35.0-235.6 GBq/mmol), and the radiochemical purity was 91.6% 6 1.5% (range, 90.1%-94.4%).…”
Section: Radiopharmaceutical Preparationmentioning
confidence: 99%